Penerapan Evaluasi Pembelajaran dalam Mata Pelajaran IPA Kelas V dengan Menggunakan Model Pembelajaran Kooperatif Tipe Group Investigation di SDN Mauk 1 Kecamatan Mauk - Ina Magdalena; Nur Ainun; Rifda Nur Nabila; Muhammad Muhaimin Aziz (RC-INSTITUT, 2020)
The purpose of this study was to improve the learning outcomes of fifth-grade students through the application of cooperative learning models of classroom investigation for science subjects at SDN Mauk. The study used was classroom action research (CAR) whit the type of qualitative research. The subjects in this consisted of 28 students 15 male students 13 female students. Data collection techniques used were observation and interviews to learn the feasibility of learning models in learning science. The percentage of completeness student learning outcomes by 64,4% and an increase of 81,7%. Can be concluded by applying the cooperative learning model of group investigation type can improve the learning outcomes of the fifth-grade science students in SDN Mauk 1.